The Representation of Moral Values in Indonesian Grade 7 English Course Books: A Multimodal Content Analysis of Prescribed Student Profiles - Primita Arif Carabella; Ashadi Ashadi (Universitas Pendidikan Mandalika, 2026)
Moral education has become an important concern in English Language Teaching (ELT) materials, as coursebooks are expected to support both language development and learners’ character formation. In Indonesia, this role is reflected in the prescribed Student Profiles. This study aims to examine how moral values are represented in Indonesian Grade 7 English coursebooks from a multimodal perspective. Employing qualitative content analysis, the study analyzes three widely used coursebooks, namely English for Nusantara, Bright an English, and Interactive English, using Kress and van Leeuwen’s (2006) multimodal framework and the six dimensions of the prescribed Student Profiles. The findings reveal that moral values are conveyed both explicitly and implicitly through verbal texts, visual images, and learning activities; however, their distribution is uneven, with certain values consistently prioritized while others remain marginal. The analysis also shows differing orientations toward local and global moral values across the coursebooks. These findings suggest that although multimodal resources enrich moral meaning-making, their effectiveness depends on pedagogical framing and opportunities for critical engagement. The study concludes that a more balanced and critically mediated integration of moral values is needed to better support learners’ moral development, with implications for coursebook design and classroom practice.